The Effect of Breastfeeding Calendar Training on Knowledge and Attitudes of Mothers in Exclusive Breastfeeding - Ari Indra Susanti; Aminarista Aminarista; Neneng Martini; Nur Rahmah; Sri Astuti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Lactating mothers were successful in giving exclusive breastfeeding as much as 42% based on SDKI (Survei Demografi Kesehatan Indonesia) in 2012. This is depend on the support of husbands and families as well as health workers. Thus, the husband or family should remind and motivate mothers as well as monitor the breastfeeding activity every day for 6 months using breastfeeding calendar.Objectives: This study aimed to determine the increase in knowledge and attitudes of mothers in providing exclusive breastfeeding after the exclusive breastfeeding calendar training.Materials and Methods: The research design used a quasi-experimental one group pre-test post-test design. This research was conducted on mothers who had babies (age 0-12 months) in Pasawahan Village and Pasawahan Kidul Village, Pasawahan District, Purwakarta Regency in April to November 2018, with 96 respondents. The sampling technique was conducted by purposive sampling. Data were collected by giving questionnaires to respondents, before and after the breastfeeding calendar training were given. The Wilcoxon test was used for the analysis of the data in this study.Results: The results showed that there were differences in the knowledge of mothers before and after training on breastfeeding calendar (p <0,000) and there were differences in the attitudes of mothers before and after the training on breastfeeding calendar (p <0,000).Conclusions: There was an increase in knowledge and changes in the attitude of mothers towards exclusive breastfeeding after being given the breastfeeding Calendar training. Therefore, suggestions for health workers, especially midwives and nutrition workers, can use the breastfeeding calendar as an educational medium to increase husband and family support in exclusive breastfeeding.